A novel GABRB3 variant in Dravet syndrome: Case report and literature review. Issue 11 (18th September 2020) - Pavone, Piero; Pappalardo, Xena Giada; Marino, Simona D.; Sciuto, Laura; Corsello, Giovanni; Ruggieri, Martino; Parano, Enrico; Piccione, Maria; Falsaperla, Raffaele
Abstract: Background: Mutations in GABRB3 have been identified in subjects with different types of epilepsy and epileptic syndromes, including West syndrome (WS), Dravet syndrome (DS), Lennox‐Gastaut syndrome (LGS), myoclonic‐atonic epilepsy (MAE), and others. Methods and results: We herewith report on a girl affected by DS, who has been followed from infancy to the current age of 18 years. Next‐generation sequencing (NGS)‐based genetic testing for multigene analysis of neurodevelopmental disorders identified two likely de novo pathogenic mutations, a missense variant in GABRB3 gene (c.842 C>T; p.Thr281IIe) and a nonsense variant found in BBS4 gene (c.883 C>T; p.Arg295Ter). Conclusion: A likely relationship between the novel GABRB3 gene variant and the clinical manifestations presented by the girl is proposed. Previously, one case of DS and two of DS‐like linked with GABRB3 mutations have been reported. To the best of our knowledge, this is the first report of DS associated with this novel variant. A literature review of clinical cases with various types of epileptic encephalopathies (EEs) related to GABRB3 mutations is reported. Abstract : Our study explores a likely new gene‐phenotype relationship between a novel GABRB3 gene variant and the clinical manifestations of Dravet syndrome (DS). We, herewith, report on a long‐term follow‐up of a girl affected by DS, who harbors a novel likely pathogenic variant of GABRB3. A literature review of cases with various types of epileptic encephalopathy related to GABRB3 mutations is discussed.